Inventory and Supply Chain Planning Systems as Drivers of Supply Chain Resilience: Analyses of Firm Performance Through the COVID-19 Pandemic - Swink, Morgan; Kovach, Jeremy J; Roh, Joseph (Production and Operations Management, 2025)
We combine insights from information processing theory (IPT), supply chain resilience literature, and collaboration with a leading supply chain planning technology provider to study the effects of excess inventory (a buffering tactic) and usage of supply chain planning systems (SCPSs) (a bridging technology) on supply chain resilience. Utilizing the exogenous disruptions caused by the COVID-19 pandemic as the setting for quasi-natural experiments, we compare profit impact and time-to-recover across manufacturing firms that operated with varied levels of inventory and SCPS use in the period leading up to the onset of the pandemic. The results of multiple tests provide no evidence that inventory buffering aided firms in being more resilient, even for firms in industries that experienced positive demand shocks during the pandemic. In contrast, we find that firms that used SCPS evidenced fewer negative financial impacts throughout the disruptive period, and they recovered faster than their peers. The results are robust to sample characteristics, time frame, and control-group matching procedures. Our study extends a growing literature on supply chain resilience by offering a more refined explanation of IPT in a disruptive context, highlighting the limitations of inventory as a buffering tactic, and describing how SCPSs help planners cope with uncertainty and disruptions. In addition, interviews with managers from a leading SCPS provider and from user firms highlight specific ways in which SCPSs provide faster and more effective responses to disruptions. We discuss the implications of these findings for future research.